Peningkatan Hasil Belajar Siswa melalui Metode Fun Learning dalam Pembelajaran Tematik - Eli Mufidah; Nurul Aminatus Sa’diyah (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2020)
The phenomenon that occurs in one of the Sekaran Public Elementary Schools shows that students have decreased learning outcomes in Thematic learning and have not achieving the minimum completeness criteria (KKM) value. Students are less enthusiastic in participating in learning because of their low learning motivation, even some students do not want to learn and do not want to go to class. This study aims to describe the effect of the Fun learning method in “Kebersamaan” theme to improve student learning outcomes in grade II in Sekaran State Elementary School. This study uses the research design